Implementation of Data Acquisition System with a Free Cooling Unit (FCU) Controller For a BTS - Mohammed Qayamuddin, Imthiazunnisa Begum, Zeeshan Ahmed Korani Ravinde MD Abdul Khader (International Journal of Scientific Research and Management (IJSRM), 2013)
— The scarcity of electricity causing serious dislocation in all spheres of life, including productionin agricultue and industries as well as in the section of cellular communication. To reduce the wastage ofelectricity in BTS room now-a-days celluler operators are using different ventilation systems instead of AirConditioner (AC). Recently many operators like Banglalink, a leading telecom operator in Bangladesh areinterested to interface a data acquisition system with these ventilation systems in BTS rooms.So in thispaper a modern ventilation system FCU is designed interfacing with a Micro SD card for data acquisitionespecially for Banglalink BTS. FCU is an electronic instrument that records the temperature data and takesdecision according to that data. This research work deals with the PIC18F4520 which includes 10 bit ADCfor data conditioning and 32K bytes of program memory which provides the advantage of interfacing aFAT-16 system with microprocessor. In display section 4X20 LCD display is used for user interaction